Rab3GEP is the non-redundant guanine nucleotide exchange factor for Rab27a in melanocytes - Figueiredo, Ana C. (2022)
Rab GTPases regulate discrete steps in vesicular transport pathways. Rabs require activation by specific guanine nucleotide exchange factors (GEFs) that stimulate the exchange of GDP for GTP. Rab27a controls motility and regulated exocytosis of secretory granules and related organelles. In melanocytes, Rab27a regulates peripheral transport of mature melanosomes by recruiting melanophilin and myosin Va. Here, we studied the activation of Rab27a in melanocytes. We identify Rab3GEP, previously isolated as a GEF for Rab3a, as the non-redundant Rab27a GEF. Similar to Rab27a-deficient ashen melanocytes, Rab3GEP-depleted cells show both clustering of melanosomes in the perinuclear area and loss of the Rab27a effector Mlph. Consistent with a role as an activator, levels of Rab27a-GTP are decreased in cells lacking Rab3GEP. Recombinant Rab3GEP exhibits guanine nucleotide exchange activity against Rab27a and Rab27b in vitro, in addition to its previously documented activity against Rab3. Our results indicate promiscuity in Rab GEF action and suggest that members of related but functionally distinct Rab subfamilies can be controlled by common activators.